Eternal : Zachary's story - Smith, Cynthia Leitich (Eternal, 2013)
"When Miranda's guardian angel Zachary recklessly saves her from falling into an open grave and dying, the result is that she turns into a vampire and he is left to try to reinstate his reputation by finally doing the right thing"--From text edition.